microRNAs and Their Targets in Apple (Malus domestica cv. “Fuji”) Involved in Response to Infection of Pathogen Valsa mali - Feng, Hao; Xu, Ming; Zheng, Xiang; Zhu, Tongyi; Gao, Xiaoning; Huang, Lili (Frontiers in Plant Science, 2017)
miRNAs are important regulators involving in plant-pathogen interactions. However, their roles in apple tree response to Valsa canker pathogen (Valsa mali, Vm) infection were poorly understood. In this study, we constructed two miRNA libraries using the twig bark tissues of apple tree (Malus domestica Borkh “Fuji”) inoculated with Vm (IVm) and PDA medium (control, BMd). Among all detected miRNAs, 23 miRNAs were specifically isolated from BMd and 39 miRNAs were specifically isolated from IVm. Meanwhile, the expression of 294 miRNAs decreased; and another 172 miRNAs showed an increased expression trend in IVm compared with that in BMd. Furthermore, two degradome sequencing libraries were also constructed to identify the target genes of these miRNAs. In total, 353 differentially expressed miRNAs between IVm and BMd were detected to be able to target 1 077 unigenes with 2 251 cleavage sites. Based on GO and KEGG analysis, these genes were found to be mainly related to transcription regulation and signal transduction. In addition, we selected 17 miRNAs and 22 corresponding target genes to screen the expression profiles when apple twigs were infected by Vm. The expression trends of most miRNAs/target genes were consist with the results of deep sequencing. Many of them may involve in the apple twig-Vm interaction by inducing/reducing their expression. What’s more, miRNAs and their target genes regulate the apple twig-Vm interaction by forming many complicated regulation networks rather than one to one model. It is worth that a conserved miRNAs mdm-miR482b, which was down regulated in IVm compared with BMd, has 14 potential target genes, most of which are disease resistance related genes. This indicates that mdm-miR482b may play important roles in apple twig response to Vm. More important, the feedback regulation of sRNA pathway in apple twig is also very complex, and play critical role in the interaction between apple twig and Vm based on the results of expression analysis. In all, the results will provide insights into the crucial functions of miRNAs in the woody plant, apple tree-Vm interaction.